Human Rights and the Environment - Karski, Leszek (Studia Ecologiae et Bioethicae, 2006)
There should be no doubt that human activities can cause serious environmental harm, or that those harms, in turn, often result in very grave consequences to human beings. Put positively, a clean and healthy environment is essential to the realization of fundamental human rights. Some advocates argue that the right to a clean environment belongs to the third generation of rights. Others noted that it is separated the fourth generation of rights. It is necessary to reflect on a source of environmental rights. It is important to search for the satisfactory meaning of the right to a clean environment. This article shows repeated and increasing recognition of a human rights-based approach to environmental protection. Such recognition demonstrates that environmental rights are emerging as an important component of international law and Polish law. At the national and international levels, the right to a healthy environment (or a related formulation) has played an important role in fostering connections between human rights and environmental approaches. The increasing practice of substantively upholding and encouraging respect for the right to a clean environment is important and should be recognized and strengthened.